1999
DOI: 10.1080/014186199251256
|View full text |Cite
|
Sign up to set email alerts
|

In-situ transmission electron microscopy study of the dislocation accommodation in [101] tilt grain boundaries in nickel bicrystals

Abstract: The relaxation of stresses associated to extrinsic grain-boundary dislocations (EGBDs) in singular Sˆ3, {111}, in vicinal Sˆ11, {311} and in general Sˆ11, {332} grain boundaries (GBs) has been investigated by in-situ transmission electron microscopy (TEM) using weak-beam conditions. In a singular Sˆ3, {111} GB, reactions of combination and annihilation occur between extrinsic and intrinsic dislocations when they initially intersect each other. These reactions yield the parallelism of the two types of dislocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Such GBDs can be localized or spread along the boundary plane [4,5,[16][17][18][19][20][21][22][23][24] depending on the degree of order along the boundary and temperature. Pestman et al showed that transmission versus absorption depends strongly on the structure of the grain boundary and that predictions for long-period boundaries could be possible using the structural unit model [5].…”
Section: The Angle Between the Lines Of Intersection Between The Incomentioning
confidence: 99%
See 1 more Smart Citation
“…Such GBDs can be localized or spread along the boundary plane [4,5,[16][17][18][19][20][21][22][23][24] depending on the degree of order along the boundary and temperature. Pestman et al showed that transmission versus absorption depends strongly on the structure of the grain boundary and that predictions for long-period boundaries could be possible using the structural unit model [5].…”
Section: The Angle Between the Lines Of Intersection Between The Incomentioning
confidence: 99%
“…Grain-boundary motion generally occurs by the motion of extrinsic GBDs [38], which can be generated by the interactions of grain boundaries with lattice dislocations [16][17][18][19][20][21][22][23][24]. Since GBDs can be mobile, the true equilibrium position of any GBD nucleated within the atomistic region could be outside the atomistic region somewhere in the continuum domain of the computational model.…”
Section: Modelling Approach: Cadd Modelmentioning
confidence: 99%